Regulation of mTOR by phosphatidic acid. (March 2023) - Frias, Maria A.; Hatipoglu, Ahmet; Foster, David A.
Highlights: Mammalian target of rapamycin complex 1 (mTORC1) plays a crucial role in cellular physiology. Amino acids lead to mTORC1 lysosomal translocation where it is activated by growth factors via Rheb. Phospholipase D (PLD) and its lipid metabolite phosphatidic acid (PA) are required for both amino acid and growth factor input to mTORC1. PA induces mTORC1 lysosomal translocation and activation in the absence of amino acids, Rag GTPases, growth factors, and Rheb. We review recent structural findings and propose that PA binds to a highly conserved sequence on the α4 helix of the FK506 binding protein 12 (FKB12)/rapamycin-binding (FRB) domain of mTOR. Crucially, by binding to two adjacent positively charged amino acids, PA disrupts the helix, with consequences for substrate binding and catalytic activity. Disruption of the α4 helix by PA allows binding of S6K to the FRB domain, but not of PRAS40 or rapamycin. It also induces FRB conformational changes that allow mTORC1 catalytic activity in the absence of Rheb. Abstract: mTORC1, the mammalian target of rapamycin complex 1, is a key regulator of cellular physiology. The lipid metabolite phosphatidic acid (PA) binds to and activates mTORC1 in response to nutrients and growth factors. We review structural findings and propose a model for PA activation of mTORC1. PA binds to a highly conserved sequence in the α4 helix of the FK506 binding protein 12 (FKBP12)/rapamycin-binding (FRB) domain of mTOR. It is proposed that PA binding to two adjacent positively charged amino acids breaks and shortens the C-terminal region of helix α4. This has profound consequences for both substrate binding and the catalytic activity of mTORC1.